High Resolution Mass Spectroscopy-Based Secondary Metabolite Profiling of Nymphaea nouchali (Burm. f) Stem Attenuates Oxidative Stress via Regulation of MAPK/Nrf2/HO-1/ROS Pathway - Md Badrul Alam; Marufa Naznin; Syful Islam; Fanar Hamad Alshammari; Hee-Jeong Choi; Bo-Rim Song; Sunghwan Kim; Sang-Han Lee (MDPI AG, 2021)
The secondary metabolites profiling of Nymphaea nouchali stem (NNSE) extract was carried out using a high-resolution mass spectroscopic technique. The antioxidant effects of NNSE, as well as the underlying mechanisms, were also investigated in tert-butyl hydroperoxide (t-BHP)-stimulated oxidative stress in RAW264.7 cells. Tandem mass spectroscopy with (−) negative mode tentatively revealed the presence of 54 secondary metabolites in NNSE. Among them, phenolic acids and flavonoids were predominant. Phenolic acids (brevifolincarboxylic acid, p-coumaroyltartaric acid, niazinin B, lalioside, 3-feruloylquinic acid, and gallic acid-O-rutinoside), flavonoids (elephantorrhizol, apigenin-6-C-galactoside 8-C-arabinoside, and vicenin-2), sialic acid (2-deoxy-2,3-dehydro-N-acetylneuraminic acid), and terpenoid (α-γ-onoceradienedione) were identified in NNSE for the first time. Unbridled reactive oxygen species/nitrogen species (ROS/RNS) and redox imbalances participate in the induction and development of many oxidative stress-linked diseases. The NNSE exhibited significant free radical scavenging capabilities and was also able to reduce t-BHP-induced cellular generation in RAW264.7 cells. The NNSE prevented oxidative stress by inducing the endogenous antioxidant system and the levels of heme oxygenase-1 (HO-1) by upregulating Nrf2 through the modulation of mitogen-activated protein kinases (MAPK), such as phosphorylated p38 and c-Jun N terminal kinase. Collectively, these results indicate that the NNSE exhibits potent effects in preventing oxidative stress-stimulated diseases and disorders through the modulation of the MAPK/Nrf2/HO-1 signaling pathway. Our findings provide new insights into the cytoprotective effects and mechanisms of Nymphaea nouchali stem extract against oxidative stress, which may be a useful remedy for oxidative stress-induced disorders.